Analysis Of Indicators Of Physical Development Of Adolescents In Various Regions Of The Republic Of Uzbekistan With Different Environmental Pollution - Ilyasova G.K. (Zien Journals, 2024)
The influence of environmental factors on the growth rate of a child's body is quite clearly traced. Among these factors are nutrition and vitamin provision, physical activity and emotional stress, acute and chronic diseases, the influence of climatic and geographical conditions, etc. At the same time, environmental factors can slow down or accelerate growth processes, but in general the growth trend is quite stable, it obeys the law of growth conservation
Keywords: obeys; growth; provision; acute